2015
DOI: 10.1016/j.virol.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus membrane penetration: Tickling the tail of a sleeping dragon

Abstract: As is the case for nearly every viral pathogen, non-enveloped viruses (NEV) must maintain their integrity under potentially harsh environmental conditions while retaining the ability to undergo rapid disassembly at the right time and right place inside host cells. NEVs generally exist in this metastable state until they encounter key cellular stimuli such as membrane receptors, decreased intracellular pH, digestion by cellular proteases, or a combination of these factors. These stimuli trigger conformational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 104 publications
0
43
0
1
Order By: Relevance
“…In vitro studies have shown that Ads attach to these cells by the interaction of the viral fiber knob with CAR, leading to the exposure of membrane-lytic protein VI ( 13 ). Viruses are subsequently internalized via receptor-mediated endocytosis, escape to the cytosol, and import viral DNA into the nucleus ( 12 , 14 17 ). In liver cells in vivo , Ad particles can also be internalized via binding to cell membrane heparan sulfate proteoglycans through blood factors ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that Ads attach to these cells by the interaction of the viral fiber knob with CAR, leading to the exposure of membrane-lytic protein VI ( 13 ). Viruses are subsequently internalized via receptor-mediated endocytosis, escape to the cytosol, and import viral DNA into the nucleus ( 12 , 14 17 ). In liver cells in vivo , Ad particles can also be internalized via binding to cell membrane heparan sulfate proteoglycans through blood factors ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence points to endosomal lipases and cholesterol transfer proteins such as the Niemann-Pick transporter playing a role in the process [80]. In addition, the viral cargo itself could facilitate this rupture as many non-enveloped viral capsid proteins including the adenovirus protein VI, rotavirus VP5 and the VP4 proteins from rhinovirus and HAV, under acidified conditions (such as those that would be encountered within endosomes), undergo conformational changes that are sufficient to penetrate and disrupt membranes [81-84]. …”
Section: Widespread Role For Membranes In Facilitating Non-lytic Viramentioning
confidence: 99%
“…Niemann–Pick transporter) permeabilize the membrane [19]. Notably, many non-enveloped virus capsid proteins including the adenovirus protein VI, the rotavirus VP5 and the poliovirus VP4 proteins have intrinsic membrane disrupting activities that can be triggered upon acidification of their environment [21–23]. Hence upon engagement and internalization into an acidified compartment, the viral particles themselves may be able to directly facilitate lysis of their vesicle membrane.…”
Section: Introductionmentioning
confidence: 99%